Energy consumption and investments for economic growth in Southern Africa Development Community (SADC) - Waite, Cleidy Nádia Abrão (2020)
This study analyses the relation between the renewable and fossil energy consume and the economic growth, as well as the relation that the total investment has with the economic growth in 10 countries from the Southern Africa Develop Community (SADC). The autoregressive method (ARDL) was used to capture the effects on a short and long run and the Driscoll Kraay estimator was used to obtain robust results. As for the remaining complementary tests it is verified the presence of heteroscedasticity, contemporaneous correlation, autocorrelation of first order and cross sectional dependence. The result shows that the fossil fuel energy consume on a short run, has been contribution to the economic growth. While the renewable energy consume in a long run presents a negative result in economic growth, this effect can be caused by the application of energy from renewable sources in non-productive activities. The total investment shows that it can be a big boost to economic growth of the countries under this study on a short and long run. The preliminary version of this work was presented in the 3th Annual Conference about Energy Transition: European and Global Perspectives, organized by Hellenic Association for Energy Economics (HAEE) in Greece.